Pengaruh Kualitas Layanan Customer Service, Kepuasan Nasabah dan Kepercayaan Nasabah dalam Meningkatkan Loyalitas Nasabah PT Bank Negara Indonesia (Persero) Tbk Kantor Cabang Surakarta - Nungki Endra Maretha; Wagiyem (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The intensification of competition in the banking sector has driven a strategic focus shift towards building and maintaining customer loyalty. This study aims to analyze the influence of customer service quality, customer satisfaction, and customer trust on customer loyalty at PT Bank Negara Indonesia (Persero) Tbk Surakarta Branch Office. Using a quantitative associative approach, the research involved 100 respondents selected through accidental sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression. The results showed that customer service quality, customer satisfaction, and customer trust simultaneously have a significant effect on customer loyalty with a determination coefficient of 79.2%. Partially, all three independent variables positively and significantly influence customer loyalty, with customer satisfaction as the dominant factor (coefficient 0.493), followed by customer service quality (0.387), and customer trust (0.135). These findings imply that efforts to increase customer loyalty must consider these three aspects in an integrated manner, with priority on strengthening customer satisfaction through improving service quality and reinforcing trust. Banks need to develop comprehensive strategies that include customer service training, responsive complaint management systems, transaction transparency, and customer education programs to enhance customer loyalty amid increasingly fierce competition.